Treatment of refractory immune-mediated necrotizing myopathy with efgartigimod - MengTing Yang; JingChu Yuan; YiKang Wang; HongJun Hao; HongJun Hao; Wei Zhang; Wei Zhang; ZhaoXia Wang; ZhaoXia Wang; Yun Yuan; Yun Yuan; YaWen Zhao (Frontiers in Immunology)
ObjectiveWe aimed to explore the efficacy and safety of efgartigimod in patients with refractory immune-mediated necrotizing myopathy (IMNM).MethodsThis open-label pilot observational study included seven patients with refractory IMNM, all of whom received intravenous efgartigimod treatment. The clinical response was assessed after 4 weeks of efgartigimod treatment according to the 2016 American College of Rheumatology–European League Against Rheumatism response criteria for adult idiopathic inflammatory myopathy. Serum levels of immunoglobulin as well as anti–signal recognition particle (SRP) and anti–3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) antibodies were measured using enzyme-linked immunosorbent assays and commercial line immunoblot assays. Safety assessments included evaluations of adverse events and severe adverse events.ResultsThe seven patients with refractory IMNM included five cases with anti-HMGCR antibodies and two cases within anti-SRP antibodies. Four of the seven patients achieved clinical responses. The total improvement score for the responders at 4 weeks were 32.5, 40.0, 47.5, and 70.0, and those at 8 weeks were 27.5, 47.5, 57.5, and 70.0. In comparison to the responsive patients, the non-responsive patients had longer durations [8 (-) versus 2 (1–5) years, P = 0.03], and more chronic myopathic features by muscle biopsy (67% versus 0%, P = 0.046). Serum immunoglobulin G levels (11.2 ± 2.5 versus 5.7 ± 2.5, P = 0.007) and anti-HMGCR/SRP antibody levels (97.2 ± 6.9 versus 41.8 ± 16.8, P = 0.002) were decreased after treatment compared with baseline levels. Adverse events were reported in one of the seven patients, who showed mild headache.ConclusionsDespite its small size, our study demonstrated that promoting the degradation of endogenous immunoglobulin G may be effective for patients with IMNM. Efgartigimod may be a promising option for cases of refractory IMNM to shorten duration and minimize chronic myopathic features.